Development of pumpkin seed meal biscuits - Gao, Dan; Helikh, Anna; Duan, Zhenhua; Liu, Yan; Shang, Feifei (Eastern-European Journal of Enterprise Technologies, 2022)
Biscuits are common snacks, which have a wide variety of flavors. With the enhancement of modern health awareness, regular biscuits with high sugar, oil, fat and low protein cannot meet the demand of customers. Customers need more healthy biscuits in the market. In this study, pumpkin seed meal, konjac along with low-gluten wheat powder were used as the main material and maltitol was added as a sweetener to make a kind of healthy biscuits with high protein, high dietary fiber and low sugar. Pumpkin seed meal is a by-product of the oil production from pumpkin seed, which has high protein content. Pumpkin seed protein is composed of albumin, globulin, glutenin, and proline. It contains high-quality protein and necessary amino acids for people. Konjac is rich in dietary fiber, which can promote intestinal peristalsis. Maltitol is a healthy sugar substitute. Both of them have a low calorie level. In this study, the effects of the addition ratio of the main material (low-gluten wheat powder, pumpkin seed meal, and konjac powder), the addition ratio of plant oil and butter, and the addition amount of maltitol on the flavor and hardness of the biscuits were analyzed by a single-factor test. Besides, the orthogonal test was conducted, and the results showed that the optimal formula was the ratio of the main material (low-gluten wheat powder, pumpkin seed meal, and konjac powder) of 2:1:1, the amount of plant oil and butter of 4 % and 12 %, and maltitol amount of 20 %. According to the nutritional determination, the pumpkin seed meal biscuits contain 20.4 % protein, 18.0 % fat, 1.8 % ash, 59.2 % total carbohydrate (including 19.1 % dietary fiber and 40.1 % available carbohydrate), and 0.6 % water